2022
DOI: 10.3389/fendo.2022.913334
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence on the impact of the COVID-19 pandemic on paediatric endocrine conditions

Abstract: Severe acute respiratory coronavirus 2 (SARS-CoV-2) interacts with the host cells through its spike protein by binding to the membrane enzyme angiotensin-converting enzyme 2 (ACE2) and it can have a direct effect on endocrine function as ACE2 is expressed in many glands and organs with endocrine function. Furthermore, several endocrine conditions have features that might increase the risk of SARS-CoV-2 infection and the severity and course of the infection, as obesity for the underlying chronic increased infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…did not report any difference in the percentage of abnormal TSH tests in childhood in the 2 periods [ 6 ]. This can be partly explained by the lower spread rate of SARS-CoV-2 infection among the paediatric population [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…did not report any difference in the percentage of abnormal TSH tests in childhood in the 2 periods [ 6 ]. This can be partly explained by the lower spread rate of SARS-CoV-2 infection among the paediatric population [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak of the pandemic, it has been stated that SARS-CoV-2 binds to angiotensin-converting enzyme 2 (ACE2) receptors in the pancreas, possibly damaging islet cells and reducing insulin release[ 13 ], the description of viral infiltration in pancreatic autopsies in patients deceased owing to SARS-CoV-2 infections raised great concern[ 14 , 15 ]. On the other hand, it has been proven that SARS-CoV-2 enters other cells of the endocrine system, such as the thyroid and the gonads, as the ACE2 receptor is also expressed in these tissues[ 16 ]. The selective destruction of the β-cells was initially seen as a contributing factor in the worsening of metabolic control of many diabetic patients during the SARS-CoV-2 infection: In other words, the severe DKA that were observed during and after the infection in adult diabetic patients was supposed to be a clinical indicator of a lack of insulin due to β-cell loss or malfunction[ 17 , 18 ].…”
Section: Epidemiology Of Type 1 Diabetesmentioning
confidence: 99%
“…In the last two decades, increasing attention has been given to the possible effects of exposure to EDCs during pre-natal and early post-natal life, and puberty ( 90 ). EDCs seem to be involved in changes in pubertal timing, although the complexity of exposure in real life makes it difficult to establish a direct causality ( 13 , 14 , 91 95 ). In a Belgian retrospective study on 145 patients, detectable concentrations of organochloride pesticides were found in foreign children, both adoptees and immigrants who were referred for CPP, whereas native Belgian children had undetectable serum levels ( 12 ).…”
Section: Precocious Puberty In Adopted Children: Current Data and Hyp...mentioning
confidence: 99%
“…However, most of these hypotheses do not apply to girls presenting with CPP during the covid-19 pandemic ( 13 ). Different hypotheses have been put forward, suggesting both direct and indirect stimulating factors ( 13 , 14 ). However, the underlying mechanisms are uncertain and no one factor can explain the dramatic increase in CPP observed during the covid-19 pandemic in girls.…”
Section: Introductionmentioning
confidence: 99%